United Republic of Tanzania : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic has negatively impacted Tanzania's macroeconomic outlook. The Tanzanian authorities are implementing a comprehensive emergency pandemic response plan to help mitigate the significant socioeconomic and health effects of the crisis, resulting in an ongoing urgent balance of payments need.